SIRT1 negatively regulates amyloid-beta-induced inflammation via the NF-κB pathway - Cao,L. (2013)
Chronic inflammation induced by amyloid-beta (Aβ) plays a key role in the development of age-related macular degeneration (AMD), and matrix metalloproteinase-9 (MMP-9), interleukin (IL)-6, and IL-8 may be associated with chronic inflammation in AMD. Sirtuin 1 (SIRT1) regulates inflammation via inhibition of nuclear factor-kappa B (NF-κB) signaling, and resveratrol has been reported to prevent Aβ-induced retinal degeneration; therefore, we investigated whether this action was mediated via activation of SIRT1 signaling. Human adult retinal pigment epithelial (RPE) cells were exposed to Aβ, and overactivation and knockdown of SIRT1 were performed to investigate whether SIRT1 is required for abrogating Aβ-induced inflammation. We found that Aβ-induced RPE barrier disruption and expression of IL-6, IL-8, and MMP-9 were abrogated by the SIRT1 activator SRT1720, whereas alterations induced by Aβ in SIRT1-silenced RPE cells were not attenuated by SRT1720. In addition, SRT1720 inhibited Aβ-mediated NF-κB activation and decrease of the NF-κB inhibitor, IκBα. Our findings suggest a protective role for SIRT1 signaling in Aβ-dependent retinal degeneration and inflammation in AMD.